BIOAKTIVITAS EKSTRAK LIMBAH DAUN TEMBAKAU (Nicotiana tabacum L.) SEBAGAI INSEKTISIDA NABATI UNTUK ULAT BAWANG MERAH Spodoptera exigua HUBNER (LEPIDOPTERA: NOCTUIDAE) - , Harwanto, Prof. Dr. Ir. Edhi Martono, MSc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The utilization of plant extracts as botanical insecticides does not only affect the mortality rate, but also the development of the insectâs life stages. The aim of this study was to determine the effect of the Madura tobacco leaf extract in sublethal concentrations on the development and reproduction of the beet armyworm Spodoptera exigua. The test design was a completely randomized design (CRD), with four sublethal concentrations, i.e. LC50, LC25, LC12,5, LC6,25, and one control replicated five times. The results showed that: (1) the sublethal concentration (0.1%) had significant effect on the growth phase and life duration of the second instar larvae of S. exigua compared to the control, (2 ) the higher the concentration, the shorter the age of larvae, adult, and the eggs, (3) the life duration of the various treatments and control was 24.48 to 26.92 days, (4) the percentage of the success of the larvae until adult and the barrier of the weight between the treatments was similar, and (5) the concentration treatments do not significantly influence the reproduction variable.